2018
DOI: 10.1055/s-0038-1670681
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radioulnar Joint Replacement in the Scarred Wrist

Abstract: Background Radiocarpal or midcarpal arthritis can occur simultaneously with arthritis of the distal radioulnar joint (DRUJ), leading to functional impairment of the wrist. Treatment often involves wrist arthroplasty or arthrodesis, either with simultaneous or secondary procedures, addressing the DRUJ. Successful treatment of solitary DRUJ arthritis with DRUJ replacement has been reported. However, outcomes in patients with multiple prior wrist surgeries are lacking. Surgery in these wrists is challenging becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 30 publications
(35 reference statements)
0
26
1
Order By: Relevance
“…Galvis et al (2014) reported good results with a total wrist arthrodesis and an Aptis prosthesis, especially in patients with RA. Forearm function and objective and subjective outcomes were improved after implantation of an Aptis prosthesis in patients with a wrist arthrodesis (Lans et al, 2019). Several soft tissue complications have been reported after implantation of an Aptis prosthesis.…”
Section: Discussionmentioning
confidence: 90%
“…Galvis et al (2014) reported good results with a total wrist arthrodesis and an Aptis prosthesis, especially in patients with RA. Forearm function and objective and subjective outcomes were improved after implantation of an Aptis prosthesis in patients with a wrist arthrodesis (Lans et al, 2019). Several soft tissue complications have been reported after implantation of an Aptis prosthesis.…”
Section: Discussionmentioning
confidence: 90%
“…Lans et al found a reoperation rate of 50% in DRUJ replace-ment after multiple wrist surgeries and suggested a more distal placement of the radial component after sufficient soft tissue mobilisation. 28 Martínez Villén et al reported persisting pain in two out of five multioperated patients. 29 A higher need for additional surgery in multioperated wrists is not evident in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This must be seen in relation to the complexity of the cases with many previous surgeries and both wrist fusions and DRUJ arthroplasty. The patients in our cohort had a median of four previous procedures, as opposed to two in the study by Lans et al 14 Also, the Mayo Wrist Score is strongly influenced by wrist motion, lowering the scores in all patients in the study. Other patient-reported outcome measures scores might be more suitable for a procedure that is combined with a wrist fusion.…”
Section: Discussionmentioning
confidence: 65%
“…39 A recent paper by Lans et al reported on 14 patients with total wrist fusions and the semi-constrained Aptis implant with a median follow-up of 5.6 years. 14 The authors found an improvement in pain, pronation, supination, DASH scores, and weight-lifting capacity. Complications included two cases of superficial infection and one deep infection that required implant removal/exchange.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation